Harry Potter complete collection 8 Filme - Rowling, J. K. 1965-; Doyle, Patrick 1953- (Warner Home Video Germany, 2009)
Harry finds himself mysteriously selected as an under-aged competitor in a dangerous tournament between three schools of magic. (www.imdb.com)
Original: Großbritannien, USA 2001
Keywords: Film; DVD-Video